PENGENDALIAN BAHAN BAKU BATU SILIKA PADA PT. SEMEN PADANG - Henny Yulius; Yudi Saputra Mardani (Sekolah Tinggi Teknologi Industri Padang, 2020)
Inventory control is a very important one for the company, because without proper inventory control the company will have problems in meeting the needs of consumers both in the form of goods and services produced by the company. PT. Semen Padang has an excess amount of inventory available, which results in the company experiencing a waste of inventory. At present the inventory released by the company is still relatively large, with an average of 76,465 tons / month. The purpose of this study was to determine whether the application of the Material Requipment Planning (MRP) method could plan the inventory of silica stone raw materials was optimal. The method applied in this research is Material Requipment Planning method with Economic Order Quantity technique. The results obtained are Material Requirement Planning (MRP) with a more optimal cost EOQ method.